Vers une politique française de compensation des impacts sur la biodiversité plus efficace : défis et perspectives - Céline Jacob; Fabien Quétier; James Aronson; Sylvain Pioch; Harold Levrel (VertigO, 2015)
The idea that development impacts on biodiversity could be offset to achieve no net loss of biodiversity has been heavily criticized. While it is denounced as a license to trash by some, it is seen as an unacceptable burden or even a new tax by others. In this context, in 2012 and 2013, the French Ministry in charge of the environment published guidance on the correct implementation of the mitigation hierarchy of avoiding, reducing, and offsetting impacts on biodiversity. The guidance, aiming at achieving no net loss (NNL) of biodiversity, and preferably a net gain for currently threatened biodiversity and ecosystems, is well grounded in theory. In spite of its laudable ambition, our analysis and comparison with international experiences shows that the French policy has some critical implementation gaps that remain to be bridged. The designing and building of adequate institutional arrangements to satisfy the growing demand for offsets has been shifted down to local and regional permitting authorities, and even developers themselves. The result is a highly variable and often ineffective project per project approach, with minimal commitments. Unless the institutional and scientific challenges of supplying offsets are tackled, the likely outcome will be an expansion of “paper offsets”, and possibly a widespread license to trash as the permitting process continues to settle for a “net loss” of biodiversity from development.